Peningkatan Hasil Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa SMP Negeri 4 Balige Kabupaten Toba Melalui Media Pembelajaran Berbasis Video - Serli Gultom; Lince Sihombing; Senida Harefa; Robert Juni Tua Sitio; Meditatio Situmorang (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study was to determine the improvement of PAK and Budi Pekerti Learning Outcomes of SMP Negeri 4 Balige Toba Regency Students Through Video-Based Learning Media. The method used in this research is quantitative method, by looking at the results of pre-test and post-test learning. The population in this study were all VIII grade students of SMP Negeri 4 Balige, totaling 208 people and a sample of 28 people was determined using Purposive Sampling technique. Data collected for variable Y is as many as 15 pre-test and post-test. The results showed that there was an increase in Christian Religious Education and Ethics Learning Outcomes, as evidenced by the post-test results which were much better than the previous pre-test.